2009
DOI: 10.1080/09500690802307730
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Students’ Thinking about Familiar Phenomena: Learners’ explanations from a curriculum context where ‘particles’ is a key idea for organising teaching and learning

Abstract: . Secondary students' thinking about familiar phenomena: learners' explanations from a curriculum context where 'particles' is a key idea for organising teaching and learning. International Journal of Science Education, Taylor & Francis (Routledge), 2009, 31 (14), pp.1917-1952 Secondary students' thinking about familiar phenomena: learners' explanations from a curriculum context where 'particles' is a key idea for organising teaching and learning. Abstract:Particle models of matter are widely recognised as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Although students recognize “that objects are made from different materials, they think of these materials in terms of their characteristic perceptual properties rather than in terms of more underlying properties (such as density)” (Smith, , p. 343). That is, students describe only what they can observe (García Franco & Taber, ; Liu & Lesniak, ). At this level, students also often confuse length with area or volume and area with volume (Smith, Maclin, Grosslight, & Davis, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although students recognize “that objects are made from different materials, they think of these materials in terms of their characteristic perceptual properties rather than in terms of more underlying properties (such as density)” (Smith, , p. 343). That is, students describe only what they can observe (García Franco & Taber, ; Liu & Lesniak, ). At this level, students also often confuse length with area or volume and area with volume (Smith, Maclin, Grosslight, & Davis, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Werby (2010) qualified a p-prim as follows: (a) it is not a formally learned concept; (b) it describes a phenomenon; (c) it is a bit of knowledge based on personal observations; (d) it may be a useful problem-solving tool as a cognitive shortcut. Taber (2008) and his co-workers studied the role for p-prims in learning chemistry (Garcı ´a-Franco and Taber, (2009); Garcı ´a-Franco, 2009, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is also the case when phase changes are considered (Andersson, 1990). Garcia Franco and Taber (2009) reported that students mainly show familiarity with the particle theory of matter but limited understanding of it. Stavy and Stachel (1985) found that difficulties that children (age 5-12) experience with classifying substances into states of matter come from the fact that they perceive the solid state as something that does not easily change its shape, so objects such as sponges are harder to perceive as being solid.…”
Section: Concepts On Structure and States Of Mattermentioning
confidence: 93%